The study of slag discharge behavior of entrained-flow gasifier based on the viscosity-temperature characteristics of different types of coals. (15th May 2021) - Lin, Kuo; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Guo, Xiaolei; Liu, Haifeng
Highlights: ·The judgment basis of the slag liquid and solid thickness was discussed. ·The effect of slag viscosity characteristics to slag discharge behavior was studied. ·The behavior of axle center offset in the deviated particle deposition was studied. Abstract: The viscosity-temperature characteristics of slag were key factors in selecting the candidate coal types and the operation conditions of the entrained flow gasifier. The operating temperature was roughly estimated based on the temperature of critical viscosity (Tcv ) or the temperature corresponding to 25 Pa·s in a commercial gasifier, which led to the blockage of the tapping hole in some cases. In this study, the effects of slag viscosity-temperature characteristics on the slag discharge behavior were investigated. The effect of deviated particle deposition on slag flow characteristics was studied. The result showed that it was more reasonable to take the interface viscosity rather than the temperature of critical viscosity as the determination basis of liquid slag and solid slag thickness in the modeling process. Besides, the slag thickness increased with the critical viscosity (corresponding to the critical temperature). Compared with the critical viscosity, the evolution of the critical temperature nearly had no influence on slag thickness. The net increase of slag thickness of the tapping hole resulting from the decrease of operating temperature was higher than that of the straight portion. When the particles were deposited unevenly, the poorer the slag quality was, the more serious the axle center offset was. To reduce the occurrence of slag plugging, the operating temperature should be selected accurately based on the slag types.